HEALTH SOCIAL SECURITY ADMINISTRATION AGENCY (BPJS) SERVICES IN ANDI DJEMMA REGIONAL GENERAL HOSPITAL, NORTH LUWU REGENCY - Paresa, Gabriella; Guntur, Muhammmad; Sakawati, Herlina; Aina, Asri Nur (Jurnal Aktor, 2025)
This study aims to find out how the Social Security Organizing Agency (BPJS) Health Services at the North Luwu Regency Regional General Hospital. This type of research is a qualitative description. Data collection is done by observation, interviews and documentation. Data analysis uses interactive model analysis i.e. data condensation, data presentation and conclusion drawing. The focus of this research is based on a study presented by Zeithaml Parasuraman with five indicators, namely form/appearance, reliability, responsiveness, assurance and empathy. The results of research on BPJS Health services at Andi Djemma Regional General Hospital, North Luwu Regency show that they are included in the good category, in accordance with the indicators, namely: 1) the form/appearance is categorized quite well; 2) reliability is categorized as quite good; 3) the response/responsiveness meets expectations is categorized as good enough; 4) the guarantee is categorized as good enough; 5) Empathy is categorized as quite good